Analisis Isi Konten Instagram @Prabowo dalam Membangun Citra pada Pemilihan Presiden 2024 - Ichsan Hidayat Rifaham; Ansar Suherman; Muh. Hidayatullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine how the Instagram account @prabowo developed a strong character during the presidential era using character theory. A qualitative approach involving content analysis was used to evaluate the textual and visual elements in the analyzed Instagram posts. The findings of this study indicate that the main theme of the content is